Arliss Cutter : Bad river - Book 6 - Cameron, Marc (New York, New York : Center Point Large Print, 2024)
"In the Inupiaq village of Wainwright on the Arctic Ocean, two teenagers discover a frozen body in the permafrost wall of their familys cellar. They recognize the face through the ice. It is the face of a young woman who went missing--two years ago... In South Dakota, Arliss Cutter searches for answers surrounding his brothers mysterious death. But his visit only raises more questions without any leads. Until he returns to Alaska--and learns that his brother had something in common with the frozen body in the ice cellar... Inside the young womans pocket is a fossilized animal tooth--similar to the one Arlisss brother picked up on a trip to South Dakota. A bizarre coincidence? Or are the two connected somehow? Before Arliss can figure it out, his brothers widow and children become the targets of a brutal home invasion. Arliss arrives on the scene in time to save them--but his actions trigger a larger investigation that puts his own neck on the line. From South Dakota to Anchorage to the Inupiaq villages of the Arctic, Arliss follows this bloodstained trail of clues to a remote lodge on the banks of the Kobuk River. Here, in this unforgiving wilderness, he will find the answers he seeks. Here, in this untamed, often violent land, he will come face to face with the terrible truth-- and the man behind his brothers murder..."--
Keywords: Brothers -- Fiction; Inupiat -- Fiction; Murder -- Investigation; Fiction; Alaska -- Fiction; Detective and mystery fiction; Novels